Ecclesiastical Tidescapes: Exploring the Early Medieval Tidal World. Issue 1 (2nd January 2019) - Petts, David
Abstract : This paper explores the way in which tides contribute to the construction of complex cognitive landscapes. Drawing on the notion of assembly and process it emphasises how tidescapes are in a constant state of becoming. The early medieval monastery of Lindisfarne (Holy Island, Northumberland, UK) is used as a case study to explore the manifold ways in which tides might inculcate themselves within the lived experiences of those who lived on the island during the Anglo-Saxon period.